Sosialisasi Penegakan Hukum Terhadap Pelaku Tindak Pidana Perjudian Online Di Media Sosial Di Desa Lama Pantai Labu Sumatera Utara - Pratitis, Sugih Ayu; Rehulina, Rehulina; Harahap , Muslim; Sitorus, Andi Putra (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
The Denai Lama tourist village is the first tourism village in Deli Serdang Regency, at the initiative of the Head of the Department of Youth, Sports, Culture and Tourism of Deli Serdang Regency, H. Faisal Arif Nasution, M.Si, this tourist village was formed by involving the local village government and stakeholders to build a new tourism image in Deli Serdang Regency. This research discusses a problem that is currently rife, namely law enforcement against perpetrators of online gambling crimes on social media. Where, based on data published in online media, it is clear that in the midst of the Covid-19 pandemic, gambling is rife in Deli Serdang Regency. This is what prompted the service team to be interested in doing this PKM. By providing socialization or legal counseling to the community, the local community can understand what the legal consequences are and how to enforce the law against perpetrators of online gambling crimes on social media. So that it is hoped that the local community will not fall prey to online gambling crimes. During a visit to the Lama Pantai Labu Village, North Sumatra, it was found that the community still did not understand the law, especially regarding law enforcement against perpetrators of online gambling crimes on social media and their role and participation and the community in dealing with online gambling. So that the Implementation Team provided legal counseling to the local community regarding law enforcement against perpetrators of online gambling crimes on social media. What can the public do to prevent or overcome online gambling which is increasingly widespread. Thus, the public is aware of its role in reducing gambling crimes.